Dissecting the Role of N6-Methylandenosine-Related Long Non-coding RNAs Signature in Prognosis and Immune Microenvironment of Breast Cancer - Zhang, Jinguo; Shan, Benjie; Lin, Lin; Dong, Jie; Sun, Qingqing; Zhou, Qiong; Chen, Jian; Han, Xinghua (Frontiers in Cell and Developmental Biology, 2021)
Breast cancer (BC) represents a molecularly and clinically heterogeneous disease. Recent progress in immunotherapy have provided a glimmer of hope for several BC subtypes. The relationship between N6-Methyladenosine (m6A) modification and long non-coding RNAs (LncRNAs) is still largely unexplored in BC. Here, intention to dissect the landscape of m6A-related lncRNAs and explore immunotherapeutic value of m6A-related lncRNAs signature, we identified m6A-related lncRNAs by co-expression analysis from The Cancer Genome Atlas (TCGA), and stratified BC patients into different subgroups. Furthermore, we generated a m6A-related lncRNA prognostic signature. Four molecular subtypes were identified by consensus clustering. The Cluster 3 preferentially had favorable prognosis, upregulated immune checkpoints expression and high level of immune cells infiltration. Twenty-one m6A-related lncRNAs were applied to construct m6A-related lncRNA model (m6A-LncRM). Survival analysis and receiver operating characteristic (ROC) curves further confirmed the prognostic value and prediction performance of m6A-LncRM. Finally, high- and low-risk BC subgroups displayed significantly different clinical features and immune cells infiltration status. Overall, our study systematically explored the prognostic value of the m6A-related LncRNAs and identified a high immunogenicity BC subtype. The proposed m6A-related LncRNAs model might serve as a robust prognostic signature and attractive immunotherapeutic targets for BC treatment.